KESİRLİ HESAP OPERATÖRLERİ YARDIMIYLA SİNGÜLER KATSAYILI DİFERANSİYEL DENKLEMLERİN ÇÖZÜMÜ - ÖZTÜRK, ÖKKEŞ (Fırat Üniveristesi, 2011)
Dört bölüm olarak hazırlanan bu çalışmanın ilk bölümünde; Kesirli Türev ve İntegraller (Diferintegraller) kavramının başlangıcı, tarihi gelişimi ve literatür taraması ele alınmıştır.İkinci bölümde; Diferintegraller için temel tanım ve teoremleri içeren bazı özellikler çalışılmıştır.Üçüncü bölümde; Diferintegraller ve diferintegraller ile ilgili bazı matematik teknikler ele alınmıştır.Son bölümde; Kesirli hesap operatörleri yardımıyla singüler katsayılı diferansiyel denklemlerin çözümleri verilmiştir.Anahtar Kelimeler: Kesirli Türev ve İntegraller (Diferintegraller), Kesirli Hesap, Leibniz Formülü, N-kesirli hesap operatörü.

In the first chapter of this thesis that consists of four chapters; beginning, historical development and literature review of Fractional Derivative and Integrals (Differintegrals) were examined.In the second chapter; some properties including fundamental definitions and theorems for differintegrals were studied.In the third chapter; differintegrals and some mathematics techniques related to differintegrals were examined.In the last chapter; solutions of the singular differential equations with the help of the fractional calculus operators were given.Key words: Fractional Derivative and Integrals (Differintegrals), Fractional Calculus, Leibniz Rule, N-fractional calculus operator.
Solution of the singular differential equations via fractionall calculus operators
Keywords: Matematik